The Life of the Shaken - Svobodová, Zuzana (Forum Pedagogiczne, 2019)
Based on the analysis of texts by Jan Patočka, the author explores two concepts of human existence. The concept of three movements of life and the concept of two basic forms of life are examined in this paper, with the aim to referring to similarities and differences between them and to try to point out the essentials from these conceptions. The motivating question that gives rise to author´s efforts in this paper is: “What kind of agreement can be found between different concepts?”